Modulation of incentivized dishonesty by disgust facial expressions - Lim, Julian; Ho, Paul; Mullette-Gillman, O'Dhaniel A. (Frontiers in Neuroscience, 2015)
Disgust modulates moral decisions involving harming others. We recently specified that this effect is bi-directionally modulated by individual sensitivity to disgust. Here, we show that this effect generalizes to the moral domain of honesty and extends to outcomes with real-world impact. We employed a dice-rolling task in which participants were incentivized to dishonestly report outcomes to increase their potential final monetary payoff. Disgust or control facial expressions were presented subliminally on each trial. Our results reveal that the disgust facial expressions altered honest reporting as a bi-directional function moderated by individual sensitivity. Combining these data with those from prior experiments revealed that the effect of disgust presentation on both harm judgments and honesty could be accounted for by the same bidirectional function, with no significant effect of domain. This clearly demonstrates that disgust facial expressions produce the same modulation of moral judgments across different moral foundations (harm and honesty). Our results suggest strong overlap in the cognitive/neural processes of moral judgments across moral foundations, and provide a framework for further studies to specify the integration of emotional information in moral decision making.